Kinetic Modelling of [Ga-68]Ga-DOTA-Siglec-9 in Porcine Osteomyelitis and Soft Tissue Infections - Jødal L.; Roivainen A.; Oikonen V.; Jalkanen S.; Hansen S.B.; Afzelius P.; Alstrup A.K.O.; Nielsen O.L.; Jensen S.B. (MDPI, 2022)
Background: [Ga-68]Ga-DOTA-Siglec-9 is a positron emission tomography (PET) radioligand for vascular adhesion protein 1 (VAP-1), a protein involved in leukocyte trafficking. The tracer facilitates the imaging of inflammation and infection. Here, we studied the pharmacokinetic modelling of [Ga-68]Ga-DOTA-Siglec-9 in osteomyelitis and soft tissue infections in pigs.
Methods: Eight pigs with osteomyelitis and soft tissue infections in the right hind limb were dynamically PET scanned for 60 min along with arterial blood sampling. The fraction of radioactivity in the blood accounted for by the parent tracer was evaluated with radio-high-performance liquid chromatography. One- and two-tissue compartment models were used for pharmacokinetic evaluation. Post-mortem soft tissue samples from one pig were analysed with anti-VAP-1 immunofluorescence. In each analysis, the animal's non-infected left hind limb was used as a control.
Results: Tracer uptake was elevated in soft tissue infections but remained low in osteomyelitis. The kinetics of [Ga-68]Ga-DOTA-Siglec-9 followed a reversible 2-tissue compartment model. The tracer metabolized quickly; however, taking this into account, produced more ambiguous results. Infected soft tissue samples showed endothelial cell surface expression of the Siglec-9 receptor VAP-1.
Conclusion: The kinetics of [Ga-68]Ga-DOTA-Siglec-9 uptake in porcine soft tissue infections are best described by the 2-tissue compartment model.